Targeted Nipple Areola Complex Reinnervation: Technical Considerations and Surgical Efficiency in Implant-based Breast Reconstruction. Issue 7 (25th July 2022) - Gfrerer, Lisa; Sager, Jessica Erdmann; Ford, Olivia Abbate; Carty, Matthew J.; Verdial, Francys C.; Gadd, Michele A.; Specht, Michelle C.; Winograd, Jonathan M.; Valerio, Ian L.
Abstract : Background: Despite promising pilot study results, adoption of neurotization of immediate implant-based reconstructions has not occurred. Methods: For surgeons interested in adopting breast reinnervation techniques, we present ways to overcome initial barriers by decreasing operative time and maximizing chances of sensory recovery. Results: We discuss the combined experience at two academic teaching hospitals, where neurotization of both immediate tissue expander cases and direct-to-implant reconstructions are performed through varying mastectomy incisions. Conclusion: Initial barriers can be overcome by shortening operative time and providing an individualized reinnervation approach that aims to increase the chance of meaningful sensation.